Materials to the creation of the “Lady slipper grove” nature monument of regional importance (Altai Krai) - Elesova , N. V. (Проблемы ботаники Южной Сибири и Монголии, 2021)
Materials on the flora and vegetation of the projected nature monument of regional importance “Ladyslipper grove” are given. Flora comprises 150 species of higher vascular plants, including 4 rare species: Cypripediumcalceolus L., C. macranthon Sw., C. ventricosum Sw., Orchis militaris L. The vegetation is typical for left-bank forest-steppe:birch, aspen and birch-aspen communities in combination with steppe meadows along the edges, and steppes with Festucavalesiaca.